Relationships between Mean, Median and Mode - Sri Rejeki Dwi Putranti (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2021)
Statistics as an analysis technique can not only be used to make descriptions, but also to make estimates and generalizations. To be able to know and deepen knowledge about statistics, knowledge of research methodology must be possessed. In this study will discuss the arithmetic mean, median and mode for single data and group data, and the related relationship between arithmetic mean, median and mode. So it will be proved that the mode plus the average of the count is equal to three times the median. Keywords: mean; median; mode